The Vortex of Identity Politics in Medan City - Andre Agasi; Muhammad Fadli; Agung Suharyanto (Britain International for Academic Research (BIAR-Publisher), 2021)
The purpose of this study was to determine the Interethnic Relations and Political Power; Ethnic Identity, Political Culture and Actor Battles; and Relationships of Political Party Actors in the 2020 Medan City Election. Identity politics in the Direct Regional Head Election in Medan. A qualitative approach is used to describe and analyze the issue of identity politics in Medan City based on the issue of nationalism and religious issues. Castells' identity politics theory, as well as the Almond and verbal political culture theory, to be the basis for analyzing the data obtained in the field regarding identity politics, the role of actors / structures and their relationship to the political culture process in the 2020 Pilkada of Medan City. The results of field research found that identity politics provides a large space for the arousal of the actors to strengthen and raise the position of elites and local rulers in Medan City. The role of actors and structures is a challenge for political parties in the regions. The politics of ethnic identity that has developed in Medan City which is based on the spirit of ethnic pragmatism actually encourages ethnicity to become a soft political force with the birth of a harmonious political culture for the creation of a good democratic climate in Medan City.